Thermoplastic resin composition and molded article manufactured therefrom
By using acrylic rubber-modified graft copolymers and polymethyl methacrylate resins in thermoplastic resins, and adding anthraquinone dyes and multifunctional radical scavengers, the deficiencies in thermoplastic resins in terms of heat resistance, colorability and appearance characteristics are solved, and high-performance uncoated molded products are achieved.
Patent Information
- Application Number
- CN202380062974.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-23
- Publication Date
- 2025-04-08
AI Technical Summary
The existing uncoated thermoplastic resins have poor performance in terms of heat resistance, colorability and appearance characteristics, and cannot meet the needs of external components of vehicles exposed to external environments.
A thermoplastic resin composition based on acrylic rubber-modified graft copolymer and polymethyl methacrylate resin was used, and anthraquinone dye and a multifunctional radical scavenger were added to improve the heat resistance, colorability and appearance characteristics of the composition.
Excellent heat resistance, coloring, weather resistance and appearance characteristics of the thermoplastic resin composition are achieved, making it suitable for the manufacture of high-performance molded products that do not require additional coating.
Smart Images

Figure BDA0005291323120000021 
Figure BDA0005291323120000061 
Figure BDA0005291323120000062
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition and a molded article produced therefrom. Background Art
[0002] Recently, in line with environmental trends and cost reduction requirements, there has been a growing demand for uncoated thermoplastic resins that can be used without a coating process. Since uncoated molded articles made from uncoated thermoplastic resins can be used without further coating, uncoated thermoplastic resins should exhibit excellent scratch resistance, colorability, impact resistance, and weather resistance.
[0003] Accordingly, as an uncoated thermoplastic resin, an acrylonitrile-styrene-acrylate copolymer resin (hereinafter, ASA resin) having generally excellent impact resistance, heat resistance, weather resistance, etc. has been used, but it exhibits slightly inferior physical properties such as heat resistance, colorability, and appearance characteristics, etc. compared to ordinary thermoplastic resins used for coated molded articles, and therefore its use is limited.
[0004] In particular, vehicle exterior parts and the like are exposed to the external environment and often require excellent heat resistance (eg, a Vicat softening temperature (VST) of 100° C. or higher), but uncoated thermoplastic resins have low heat resistance and therefore cannot meet this requirement.
[0005] To solve this problem, attempts have been made to improve heat resistance by blending a polymer having excellent heat resistance (e.g., α-methylstyrene copolymer) with an uncoated thermoplastic resin, but there is another problem of reduced transparency and colorability and deterioration of appearance characteristics due to the difference in refractive index between the continuous phase (matrix) and the dispersed phase (domain).
[0006] Accordingly, research on thermoplastic resin compositions having excellent colorability, weather resistance, and appearance characteristics as well as excellent heat resistance is required. Summary of the Invention
[0007]
Technical Issues
[0008] Embodiments provide a thermoplastic resin composition having excellent heat resistance, colorability, weather resistance, and appearance characteristics, and a molded article made therefrom.
[0009]
Technical solution
[0010] According to an embodiment, a thermoplastic resin composition includes: based on 100 parts by weight of a base resin including: (A) 15 to 25 wt% of an acrylic rubber-modified graft copolymer; and (B) 75 to 85 wt% of a polymethyl methacrylate resin including 0.5 to 3 wt% of a methyl acrylate-derived component; and based on the base resin: (C) 0.1 to 1 part by weight of an anthraquinone dye; and (D) 0.1 to 0.5 part by weight of a multifunctional free radical scavenger.
[0011] (A) The acrylic rubber-modified graft copolymer may include a core comprising an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0012] The average particle size of the acrylic rubber-like polymer may be 100 nm to 250 nm.
[0013] (A) The acrylic rubber-modified graft copolymer may include a core of a butyl acrylate-styrene crosslinked copolymer and a shell formed by grafting a styrene-acrylonitrile copolymer onto the core.
[0014] (A) The acrylic rubber-modified graft copolymer may include a core of a butyl acrylate-silicone crosslinked copolymer and a shell formed by grafting a styrene-acrylonitrile copolymer onto the core.
[0015] (A) The acrylic rubber-modified graft copolymer may include a core of a butyl acrylate-styrene crosslinked copolymer and a shell formed by grafting polymethyl methacrylate onto the core.
[0016] (B) The polymethyl methacrylate resin including 0.5 to 3 wt% of a methyl acrylate-derived component may include 1 to 2 wt% of a methyl acrylate-derived component.
[0017] (D) The multifunctional free radical scavenger may include a structure represented by Chemical Formula 1:
[0018] [Chemical Formula 1]
[0019]
[0020] (In Chemical Formula 1, n is an integer of 2 to 4)
[0021] The thermoplastic resin composition may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, mold release agents, thermal stabilizers, antioxidants, UV stabilizers, pigments, and dyes.
[0022] In another embodiment, a molded article made from the thermoplastic resin composition is provided.
[0023] The molded article may have a lightness (L*) of less than or equal to 2.0 as measured according to ASTM E308 on a 2.5 mm thick sample in a specularly excluded light mode.
[0024] The molded article may have a Vicat softening temperature (VST) greater than or equal to 100° C., measured under the B50 condition according to the ISO 306 standard.
[0025] The molded article may have a color change (ΔE) of less than or equal to 2.0 before and after an aging test as measured by irradiating the molded article with an energy of 4,500 kJ according to the SAE J 1960 standard.
[0026] The molded article can have a volatile gas generation amount of less than or equal to 600 ppm by placing 4 g of the molded article in a glass petri dish having a diameter of 5 cm, covering the top with a glass plate, heating on a hot plate at 250° C. for 2 hours, and then cooling the plate temperature to room temperature, as measured by the weight increase of the glass plate.
[0027] Beneficial effects
[0028] A thermoplastic resin composition having excellent heat resistance, colorability, weather resistance and appearance characteristics, and a molded article produced therefrom can be provided. DETAILED DESCRIPTION
[0029] Hereinafter, embodiments of the present invention are described in detail. However, these embodiments are exemplary, and the present disclosure is not limited thereto.
[0030] In the present specification, unless otherwise mentioned, "copolymerization" means block copolymerization, random copolymerization or graft copolymerization, and "copolymer" means block copolymer, random copolymer or graft copolymer.
[0031] In the present specification, unless otherwise mentioned, the average particle size of the rubbery polymer refers to a volume average diameter, and means a Z-average particle size measured using a dynamic light scattering analysis instrument.
[0032] In this specification, unless otherwise mentioned, the weight average molecular weight is measured by dissolving a powder sample in an appropriate solvent and then subjecting it to gel permeation chromatography (GPC) using 1200 series manufactured by Agilent Technologies (the standard sample is polystyrene manufactured by Shodex).
[0033] The thermoplastic resin composition according to the embodiment includes, based on 100 parts by weight of a base resin comprising: (A) 15 to 25 wt% of an acrylic rubber-modified graft copolymer; and (B) 75 to 85 wt% of a polymethyl methacrylate resin comprising 0.5 to 3 wt% of a methyl acrylate-derived component, and (C) 0.1 to 1 part by weight of an anthraquinone-based dye, based on the base resin; and (D) 0.1 to 0.5 part by weight of a multifunctional radical scavenger.
[0034] Hereinafter, each component of the thermoplastic resin composition is described in detail.
[0035] (A) Acrylic rubber modified graft copolymer
[0036] The thermoplastic resin composition according to an embodiment includes (A) an acrylic rubber-modified graft copolymer. The (A) acrylic rubber-modified graft copolymer serves to enhance various properties of the thermoplastic resin composition, such as impact resistance, mechanical properties, and appearance properties.
[0037] In an embodiment, the (A) acrylic rubber-modified graft copolymer may include a core including an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from (meth)acrylate compounds, aromatic vinyl compounds, and vinyl cyanide compounds onto the core.
[0038] (A) The acrylic rubber-modified graft copolymer can be prepared by any preparation method known to those skilled in the art.
[0039] The preparation method may be a conventional polymerization method, for example, emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, etc. As a non-limiting example, it can be prepared by preparing an acrylic rubber-like polymer, and graft-polymerizing at least one selected from (meth)acrylate compounds, aromatic vinyl compounds, and vinyl cyanide compounds onto a core formed of at least one layer of the acrylic rubber-like polymer to form at least one layer of the shell.
[0040] The acrylic rubber polymer may have an average particle size of 100 nm to 200 nm, or for example, 120 nm to 180 nm. The acrylic ester compound may be, for example, ethyl acrylate, butyl acrylate, isooctyl acrylate, hexyl acrylate, or a combination thereof.
[0041] The acrylate monomers may be copolymerized with one or more other free radical polymerizable monomers in an amount of 5 to 30 wt %, or for example 10 to 20 wt %, based on the total weight of the acrylic rubbery polymer.
[0042] The average particle size of the acrylic rubber-like polymer may be 100 nm to 250 nm, for example, 100 nm to 200 nm, for example, 100 nm to 150 nm. Within the above average particle size range, the thermoplastic resin composition may have excellent impact resistance, mechanical properties, and colorability.
[0043] In an embodiment, the (meth)acrylate compound included in the shell may be at least one selected from methacrylate, acrylate, methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0044] The aromatic vinyl compound included in the shell may be at least one selected from styrene, α-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, chlorostyrene, vinyltoluene, or vinylnaphthalene, but is not limited thereto.
[0045] The vinyl cyanide compound included in the shell may be at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and fumaronitrile, but is not limited thereto.
[0046] In an embodiment, when a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound is graft-polymerized to a core including an acrylic rubber-like polymer to form a shell, the shell may be a copolymer including a monomer mixture of an aromatic vinyl compound and a vinyl cyanide compound in a weight ratio of 1:1 to 4:1 (e.g., 1:1 to 3:1).
[0047] In an embodiment, the (A) acrylic rubber modified graft copolymer may include a core of a butyl acrylate-styrene crosslinked copolymer and a shell formed by grafting a styrene-acrylonitrile copolymer (SAN) onto the core.
[0048] In an embodiment, the (A) acrylic rubber modified graft copolymer may include a core of a butyl acrylate-styrene crosslinked copolymer and a shell formed by grafting polymethyl methacrylate (PMMA) onto the core.
[0049] In an embodiment, the (A) acrylic rubber modified graft copolymer may include a core of butyl acrylate-silicone crosslinked copolymer and a shell formed by grafting styrene-acrylonitrile copolymer (SAN) onto the core.
[0050] In an embodiment, the content of the (A) acrylic rubber-modified graft copolymer may be 15 to 25 wt %, for example, 15 to 20 wt %, for example, 20 to 25 wt %, based on 100 wt % of the base resin. Within the above weight percentage range, the thermoplastic resin composition may have excellent impact resistance and colorability.
[0051] (B) polymethyl methacrylate resin comprising 0.5 to 3 wt% of a methyl acrylate derived component
[0052] The thermoplastic resin composition according to an embodiment includes (B) a polymethyl methacrylate (PMMA) resin including 0.5 to 3 wt % of a methyl acrylate-derived component, wherein the (B) polymethyl methacrylate resin can impart colorability and weather resistance to the thermoplastic resin composition.
[0053] (B) The polymethyl methacrylate resin comprising 0.5 to 3 wt% of a methyl acrylate-derived component can be obtained by polymerizing a monomer mixture comprising methyl methacrylate and methyl acrylate by a known polymerization method such as suspension polymerization, bulk polymerization or emulsion polymerization.
[0054] The thermoplastic resin composition of the present invention can ensure excellent heat resistance by including a polymethyl methacrylate resin containing 0.5 to 3 wt% of a methyl acrylate-derived component. The content of the methyl acrylate-derived component can be greater than or equal to 0.5 wt%, greater than or equal to 1 wt%, greater than or equal to 1.5 wt%, greater than or equal to 2 wt%, or greater than or equal to 2.5 wt% and less than or equal to 3 wt%, less than or equal to 2.5 wt%, less than or equal to 2.0 wt%, less than or equal to 1.5 wt%, or less than or equal to 1.0 wt%, and specifically, can be 1 to 2 wt%. Within the above weight range, the heat resistance of the thermoplastic resin composition can be further improved.
[0055] (B) The polymethyl methacrylate resin including 0.5 to 3 wt % of a methyl acrylate-derived component may have a glass transition temperature of 100 to 150°C, for example, 110 to 130°C.
[0056] The weight average molecular weight of the polymethyl methacrylate resin (B) including 0.5 to 3 wt% of a methyl acrylate-derived component may be 50,000 to 200,000 g / mol, for example, 70,000 to 150,000 g / mol. Within the above range, the scratch resistance and processability of the thermoplastic resin composition may be improved.
[0057] The content of the polymethyl methacrylate resin (B) including 0.5 to 3 wt% of a methyl acrylate-derived component may be 75 to 85 wt%, for example, 75 to 80 wt%, for example, 80 to 85 wt%, based on 100 wt% of the base resin. Within the above weight % range, the thermoplastic resin composition may have excellent colorability, heat resistance, and weather resistance.
[0058] (C) Anthraquinone dyes
[0059] The thermoplastic resin composition according to the embodiment may include (C) an anthraquinone-based dye, and (C) anthraquinone-based dye may make the thermoplastic resin composition appear black. (C) Anthraquinone-based dye may be a compound including 50 wt% or more of a component having a structure represented by Chemical Formula 2.
[0060] [Chemical Formula 2]
[0061]
[0062] In an embodiment, a dispersant can be used together with anthraquinone dye to disperse it in the thermoplastic resin composition. Specifically, the dye can be used by pre-surface-treating the dye with a dispersant, or the dispersant can be added together with the dye during the preparation of the thermoplastic resin composition.
[0063] The dispersant can be a nonionic dispersant, anionic dispersant, cationic dispersant, etc.
[0064] The (C) anthraquinone-based dye may be included in an amount of 0.1 to 1 part by weight, for example, 0.1 to 0.8 parts by weight, based on 100 parts by weight of the base resin.
[0065] (D) Multifunctional free radical scavenger
[0066] The thermoplastic resin composition according to an embodiment may include (D) a multifunctional radical scavenger, and the (D) multifunctional radical scavenger may further improve the appearance characteristics of the thermoplastic resin composition of the present invention.
[0067] When the thermoplastic resin composition includes a polymethyl methacrylate resin containing a relatively low content of 0.5 to 3 wt% of a component derived from methyl acrylate as described above, there is a problem in that when a molded article is manufactured using the thermoplastic resin composition by a method such as injection molding, viscous decomposition gas is generated, resulting in deterioration in the appearance characteristics of the molded article.
[0068] To solve this problem, the present invention includes a small amount of a multifunctional radical scavenger capable of capturing a large number of radicals in a thermoplastic resin composition, thereby improving appearance characteristics without deteriorating physical properties such as impact resistance and heat resistance.
[0069] (D) The multifunctional free radical scavenger may include a structure represented by Chemical Formula 1:
[0070] [Chemical Formula 1]
[0071]
[0072] (In Chemical Formula 1, n is an integer of 2 to 4)
[0073] Based on 100 parts by weight of the base resin, the content of the (D) multifunctional free radical scavenger can be 0.1 to 0.5 parts by weight, for example, 0.1 to 0.3 parts by weight, for example, 0.3 to 0.5 parts by weight, and within the above-mentioned range of parts by weight, the appearance characteristics of the molded article made from the thermoplastic resin composition including it can be further improved.
[0074] (E) Additives
[0075] The thermoplastic resin composition according to an embodiment may further include one or more additives, in addition to components (A) to (D), which are necessary to balance properties while not causing deterioration of other characteristics or depending on the final use of the thermoplastic resin composition.
[0076] Specifically, the additives may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, release agents, thermal stabilizers, antioxidants, UV stabilizers, dyes, and pigments.
[0077] These additives may be appropriately included within a range not impairing the characteristics of the thermoplastic resin composition, and specifically, may be included in an amount of less than or equal to about 20 parts by weight based on 100 parts by weight of the base resin, but is not limited thereto.
[0078] Meanwhile, the thermoplastic resin composition according to the embodiment may also be mixed with other resins or other rubber components and used together.
[0079] Meanwhile, another embodiment provides a molded article manufactured using the thermoplastic resin composition according to the embodiment. The molded article can be manufactured using the thermoplastic resin composition using various methods known in the art, such as injection molding or extrusion molding.
[0080] The molded article may have a lightness (L*) of less than or equal to 1.0 or less than or equal to 0.9, as measured in specular exclusion (SCE) mode according to ASTM E308 on a 2.5 mm thick sample.
[0081] The molded article may have a Vicat softening temperature (VST) greater than or equal to 100° C., greater than or equal to 101° C., greater than or equal to 102° C., or greater than or equal to 103° C., measured under B50 conditions according to ISO 306.
[0082] The molded article may have a color change (ΔE) of less than or equal to 2.0, less than or equal to 1.9, less than or equal to 1.8, less than or equal to 1.7, less than or equal to 1.6, less than or equal to 1.5, less than or equal to 1.4, less than or equal to 1.3, less than or equal to 1.2, less than or equal to 1.1, or less than or equal to 1.0 before and after the aging test, as measured by irradiating the molded article with 4,500 kJ of energy according to the SAE J 1960 standard.
[0083] The molded article may have a volatile gas generation amount of 600 ppm or less, 550 ppm or less, or 500 ppm or less, as measured by the weight increase of the glass plate by placing 4 g of the molded article in a glass petri dish having a diameter of 5 cm, covering the top with a glass plate, heating on a hot plate at 250° C. for 2 hours, and then cooling the plate temperature to room temperature.
[0084] Hereinafter, preferred embodiments of the present invention will be described. However, these embodiments should not be interpreted as limiting the scope of the present invention in any sense.
[0085] Examples 1 to 3 and Comparative Examples 1 to 6
[0086] Each of the thermoplastic resin compositions of Examples 1 to 3 and Comparative Examples 1 to 6 was prepared according to the component content ratio shown in Table 1.
[0087] The components listed in Table 1 were mixed in a conventional mixer and then extruded into a thermoplastic resin composition in pellet form using a twin-screw extruder (L / D = 29, Φ = 45 mm) at a barrel temperature of approximately 240°C. Each thermoplastic resin composition pellet was dried in a dehumidified dryer at approximately 80°C for approximately 4 hours and then injection molded using a 6-ounce injection molding machine set at a cylinder temperature of 240°C and a mold temperature of 60°C to prepare samples for property measurement. The measured properties are shown in Table 2.
[0088] In Table 1, components (A) and (B) are expressed in wt% based on the total weight of components (A) and (B), and components (C) and (D) are expressed in parts by weight based on 100 parts by weight of the base resin including components (A) and (B).
[0089] (Table 1)
[0090]
[0091] Each component in Table 1 is described below.
[0092] (A-1) Acrylic rubber modified graft copolymer
[0093] A core-shell structured graft copolymer was used, including about 50 wt% of a core comprising a butyl acrylate-styrene cross-linked copolymer having an average particle size of about 130 nm, and a shell formed by grafting a styrene-acrylonitrile copolymer (SAN) having a styrene-derived component and an acrylonitrile-derived component in a weight ratio of about 7:3 into the core (manufacturer: Lotte Chemical Corp.).
[0094] (A-2) Acrylic rubber modified graft copolymer
[0095] A core-shell structure graft copolymer including about 60 wt % of a core including a butyl acrylate-styrene crosslinked copolymer having an average particle size of about 210 nm and a shell formed by grafting polymethyl methacrylate (PMMA) onto the core (manufacturer: Kaneka Corp., product name: M-210) was used.
[0096] (A-3) Acrylic rubber modified graft copolymer
[0097] A core-shell structure graft copolymer was used, comprising about 60 wt % of a core comprising a butyl acrylate-silicone crosslinked copolymer having an average particle size of about 100 nm, and a shell formed by grafting a styrene-acrylonitrile copolymer (SAN) having a styrene-derived component and an acrylonitrile-derived component in a weight ratio of about 2:1 onto the core (manufacturer: Mitsubishi Chemical Corp., product name: SX006).
[0098] (A-4) Acrylic rubber modified graft copolymer
[0099] A core-shell structured graft copolymer was used, comprising about 50 wt% of a core comprising a butyl acrylate-styrene crosslinked copolymer having an average particle size of about 350 nm, and a shell formed by grafting a styrene-acrylonitrile copolymer (SAN) having a styrene-derived component and an acrylonitrile-derived component in a weight ratio of about 2:1 onto the core (manufacturer: Lotte Chemical Corp.).
[0100] (B-1) polymethyl methacrylate resin
[0101] A polymethyl methacrylate resin (manufacturer: Lotte MCC Corp.) having a weight average molecular weight of about 100,000 g / mol and a methyl acrylate-derived component content of about 2 wt % was used.
[0102] (B-2) polymethyl methacrylate resin
[0103] A polymethyl methacrylate resin (manufacturer: Asahi Kasei Corp.) having a weight average molecular weight of about 60,000 g / mol and a methyl acrylate-derived component content of about 5 wt % was used.
[0104] (B-3) polymethyl methacrylate resin
[0105] A polymethyl methacrylate resin (manufacturer: Trinseo) having a weight average molecular weight of about 90,000 g / mol and a methyl acrylate-derived component content of about 13% was used.
[0106] (C-1) Anthraquinone dyes
[0107] A dye containing 50 wt% or more of a component having a structure represented by Chemical Formula 2 was used (Manufacturer: Solusys Corp.)
[0108] (C-2) Carbon black
[0109] Using Orion Engineered Carbons 50L.
[0110] (D-1) Multifunctional free radical scavenger
[0111] A multifunctional radical scavenger having a structure represented by Chemical Formula 1 (manufacturer: BASF, product name: 1010).
[0112] (D-2) Phenolic free radical cleaner
[0113] A hindered phenol type monofunctional free radical cleaner (manufacturer: BASF, product name: 1076).
[0114] Characteristic evaluation
[0115] The samples for measuring characteristics according to Examples 1 to 3 and Comparative Examples 1 to 6 were measured for coloring, heat resistance, weather resistance, and appearance characteristics in the following methods, and the results are shown in Table 2.
[0116] Colorability: Lightness (L*) of a sample having a thickness of 2.5 mm was measured in a specular light exclusion (SCE) mode according to ASTM E308 using CM-3700d manufactured by Konica Minolta Inc. The lower the lightness, the better the black color, which confirms more excellent colorability.
[0117] Heat resistance (unit: °C): Vicat softening temperature (VST) was measured under B50 condition according to ISO 306 standard.
[0118] Weathering: In accordance with SAE J 1960, the sample was irradiated with 4,500 kJ of energy using Ci4000 manufactured by Atlas Material Testing Solutions, and the color change (ΔE) of the sample before and after evaluation was measured based on the glossy surface in the specular reflected light excluded (SCE) mode using CM-3700d manufactured by Konica Minolta, Inc.
[0119] Scratch resistance (unit: grade): According to JIS K5401, the pencil hardness at which no scratch is generated is measured by placing a weight of 500 g on a pencil (9B to 9H) and then pushing the pencil 5 times at a speed of 10 mm / s on a flat sample to check.
[0120] Appearance properties (unit: ppm): After measuring the weight (mg) of the upper glass plate of a 5 cm diameter glass petri dish, 4 g of the pelletized molded article was placed on the glass petri dish to measure the weight (mg), then covered with the upper glass plate, heated on a hot plate at 250°C for 2 hours, and cooled to room temperature to measure the weight increase of the upper glass plate. This was obtained as the amount of volatile gas deposited on the upper glass plate. The lower the amount of volatile gas generated, the less gas components deposited on the molded article, confirming excellent appearance properties.
[0121] (Table 2)
[0122]
[0123] Referring to the results of Tables 1 to 2, it was confirmed that the thermoplastic resin composition including components (A) to (D) and the molded article using the same exhibited excellent colorability, heat resistance, weather resistance, and appearance characteristics.
[0124] While the invention has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A thermoplastic resin composition comprising Based on 100 parts by weight of the base resin comprising the following: (A) 15 to 25 wt% of an acrylic rubber-modified graft copolymer; and (B) 75 to 85 wt% of a polymethyl methacrylate resin including 0.5 to 3 wt% of a methyl acrylate derived component, And based on the above base resin: (C) 0.1 to 1 parts by weight of anthraquinone dye; and (D) 0.1 to 0.5 parts by weight of a multifunctional free radical scavenger.
2. The thermoplastic resin composition according to claim 1, wherein (A) The acrylic rubber-modified graft copolymer includes a core comprising an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylic acid ester compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
3. The thermoplastic resin composition according to claim 2, wherein The average particle size of the acrylic rubber-like polymer is 100 nm to 250 nm.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein (A) The acrylic rubber modified graft copolymer includes a core of a butyl acrylate-styrene crosslinked copolymer, and a shell formed by grafting a styrene-acrylonitrile copolymer onto the core.
5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein (A) The acrylic rubber modified graft copolymer includes a core of a butyl acrylate-silicone crosslinked copolymer, and a shell formed by grafting a styrene-acrylonitrile copolymer onto the core.
6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein (A) The acrylic rubber modified graft copolymer includes a core of a butyl acrylate-styrene crosslinked copolymer and a shell formed by grafting polymethyl methacrylate onto the core.
7. The thermoplastic resin composition according to any one of claims 1 to 6, wherein (B) The polymethyl methacrylate resin including 0.5 to 3 wt% of a methyl acrylate derived component includes 1 to 2 wt% of a methyl acrylate derived component.
8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein (D) The multifunctional free radical scavenger comprises a structure represented by Chemical Formula 1: [Chemical formula 1] (In Chemical Formula 1, n is an integer of 2 to 4).
9. The thermoplastic resin composition according to any one of claims 1 to 8, wherein The thermoplastic resin composition further comprises at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, mold release agents, thermal stabilizers, antioxidants, UV stabilizers, pigments and dyes.
10. A molded product produced from the thermoplastic resin composition according to any one of claims 1 to 9.
11. The molded article according to claim 10, wherein The molded article has a lightness (L*) less than or equal to 1.0 as measured in accordance with ASTM E308 on a 2.5 mm thick sample in a specularly excluded light mode.
12. The molded article of claim 10 or claim 11, wherein The molded article has a Vicat softening temperature (VST) greater than or equal to 100° C., measured under B50 conditions according to ISO 306 standard.
13. The molded article according to any one of claims 10 to 12, wherein The molded article has a color change (ΔE) of less than or equal to 2.0 before and after an aging test as measured by irradiating the molded article with an energy of 4,500 kJ according to the SAE J 1960 standard.
14. The molded article according to any one of claims 10 to 13, wherein The molded article can have a volatile gas generation amount of less than or equal to 600 ppm by placing 4 g of the molded article in a glass petri dish having a diameter of 5 cm, covering the top with a glass plate, heating on a hot plate at 250° C. for 2 hours, and then cooling the plate temperature to room temperature, as measured by the weight increase of the glass plate.